The Arvon book of life writing : writing biography, autobiography and memoir - Cline, Sally (Methuen Drama, 2010)
Fascinating, wide-ranging, hugely knowledgeable - an indispensable guide and a beguiling education William Boyd Packed with insights and advice - just the inspiration to start writing! Jenny Uglow Everyone has a story This book shows how the best writers tell them, and offers advice on how to tell them yourself. Biographers Sally Cline and Carole Angier teach life writing - an area of creative writing that is exploding in popularity - at the world-famous Arvon Foundation. They have distilled the essence of their popular course on memoir, autobiography and biography into this wide-ranging bo.
Keywords: Biography as a literary form.; Autobiography -- Authorship.; Biography.; Biographies as Topic; Biographie (Genre littéraire); Biographies.; biographies (literary works); biography (general genre); LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; Literature.; Autobiography -- Authorship; Biography as a literary form; Biografie; Autobiografie; Kreatives Schreiben